2022
DOI: 10.1038/s41398-022-01949-3
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of co-occurring pain and depression: an activation-likelihood estimation (ALE) meta-analysis and systematic review

Abstract: The relationship between pain and depression is thought to be bidirectional and the underlying neurobiology ‘shared’ between the two conditions. However, these claims are often based on qualitative comparisons of brain regions implicated in pain or depression, while focused quantitative studies of the neurobiology of pain-depression comorbidity are lacking. Particularly, the direction of comorbidity, i.e., pain with depression vs. depression with pain, is rarely addressed. In this systematic review (PROSPERO r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 117 publications
1
16
0
1
Order By: Relevance
“…While similar lateralization has already been reported in the central amygdala during chronic pain 26 , 27 , especially at a later timepoint 28 , our results extend these findings to the BLA in the context of NPID. Also, a recent systematic review of 70 human imaging studies further supports our observation, as pain concomitant with depression was found to strongly associate with enhanced connectivity of the right amygdala, particularly with the prefrontal cortex 29 . Finally, as a complementary strategy to assess the connectivity of the ACC and the BLA, we took advantage of imaging data recently generated in our NPID model using resting-state functional Magnetic Resonance Imaging (rs-fMRI).…”
Section: Resultssupporting
confidence: 85%
“…While similar lateralization has already been reported in the central amygdala during chronic pain 26 , 27 , especially at a later timepoint 28 , our results extend these findings to the BLA in the context of NPID. Also, a recent systematic review of 70 human imaging studies further supports our observation, as pain concomitant with depression was found to strongly associate with enhanced connectivity of the right amygdala, particularly with the prefrontal cortex 29 . Finally, as a complementary strategy to assess the connectivity of the ACC and the BLA, we took advantage of imaging data recently generated in our NPID model using resting-state functional Magnetic Resonance Imaging (rs-fMRI).…”
Section: Resultssupporting
confidence: 85%
“…A study from Tassorelli's group demonstrated that patients with anxiety disorders are less likely to respond to anti‐CGRP mAbs (Bottiroli et al., 2021), confirming the results obtained in another study among CM sufferers treated with galcanezumab in 2020 (Smitherman et al., 2020). Pain and depression are processed by the same brain areas, thus determining a possible overlapping between the two conditions (Zheng et al., 2022), and this may explain why the two conditions are often correlated. Moreover, stating the incapability of the anti‐CGRP mAb to cross the BBB and to reach the abovementioned areas, it should be arguable that depressive symptoms may be refractory toward anti‐CGRP mAbs (Irimia et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Relevant studies have confirmed that the relationship between pain and depression is bidirectional. For the first time, a study (Zheng C J, Van Drunen S & Egorova-Brumley N., 2022) analyzed the neural correlation between pain and depression co-morbidities through ALE Meta-analysis. ALE analysis showed that pain accompanied by depression was related to the right amygdala, while depression accompanied by pain was mainly related to the left dorsolateral prefrontal cortex (DLPFC).…”
Section: Connections Of Brain Structurementioning
confidence: 99%